Heterologous prime-boost with an mRNA vaccine and an oncolytic virus enhances tumor regression through overcoming intratumoral immune suppression - Kuan Zhang; Dong Zuo; Zhenglong Wang; Jun Ding; Jiang Xu; Yin Liu; Yu Zhong; William Jia (Cell Reports)
Summary: Therapeutic mRNA vaccines are limited in inducing tumor shrinkage in advanced cancers due to their inability to overcome immune-suppressive mechanisms within tumors. In this study, we developed an HPV-immunogen-expressing oncolytic virus (OV) using HSV-1 for HPV-related cancer treatment. A mouse syngeneic tumor model evaluates the effectiveness of intratumoral OV application for E6+E7+ tumors. Comparative analysis of OV and mRNA vaccines reveals distinct mechanisms in tumor treatment. Single-cell RNA sequencing and flow cytometry show that OV enhances cytotoxic T cell infiltration, polarizes neutrophils and macrophages toward anti-tumor phenotypes, and promotes immune activation within the tumor. In contrast, the mRNA vaccine more effectively activates peripheral antigen-specific T cell responses. A heterologous prime-boost strategy using the mRNA vaccine to prime systemic T cells, followed by OV therapy to direct these cells into the tumor, leads to significant tumor regression. This combination optimizes both systemic and intratumoral immune responses for advanced HPV-related cancers.